ENHANCING ISLAMIC BANK PROFITABILITY: EVALUATING THE ROLE OF MUDHARABAH AND MUSYARAKAH FINANCING - Lutfianto; Ruhadi; Setiawan, Setiawan (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2025)
This study aims to analyze the influence of Mudharabah and Musyarakah financing on net profit in Islamic commercial banks registered with the Financial Services Authority (OJK) during the 2014–2023 period. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) as the analytical method. The results show that Mudharabah financing does not have a significant effect on net profit, while Musyarakah financing has a highly significant and positive effect. These findings indicate that Musyarakah is a more effective financing scheme in improving the financial performance of Islamic commercial banks. Therefore, financial management strategies in Islamic banks should place greater emphasis on optimizing the use of Musyarakah financing.